2009
DOI: 10.1121/1.3083233
|View full text |Cite
|
Sign up to set email alerts
|

Speech intelligibility in background noise with ideal binary time-frequency masking

Abstract: Ideal binary time-frequency masking is a signal separation technique that retains mixture energy in time-frequency units where local signal-to-noise ratio exceeds a certain threshold and rejects mixture energy in other time-frequency units. Two experiments were designed to assess the effects of ideal binary masking on speech intelligibility of both normal-hearing (NH) and hearing-impaired (HI) listeners in different kinds of background interference. The results from Experiment 1 demonstrate that ideal binary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 162 publications
(145 citation statements)
references
References 49 publications
9
131
2
1
Order By: Relevance
“…In accord with previous work involving sentences and either algorithm processing (Healy et al, 2013) or IBM processing (Anzalone et al, 2006;Wang et al, 2009), gains were greater for HI than for NH listeners and for modulated than for stationary backgrounds. The HI-listener advantage is promising because it indicates that the algorithm and the IBM are effective despite the multitude of limitations imposed by the impaired auditory system.…”
Section: Hi-listener and Babble Advantagessupporting
confidence: 74%
See 4 more Smart Citations
“…In accord with previous work involving sentences and either algorithm processing (Healy et al, 2013) or IBM processing (Anzalone et al, 2006;Wang et al, 2009), gains were greater for HI than for NH listeners and for modulated than for stationary backgrounds. The HI-listener advantage is promising because it indicates that the algorithm and the IBM are effective despite the multitude of limitations imposed by the impaired auditory system.…”
Section: Hi-listener and Babble Advantagessupporting
confidence: 74%
“…As with the algorithm, it was found that the IBM improved recognition of isolated phonemes, thus extending results observed previously for sentences (Anzalone et al, 2006;Brungart et al, 2006;Li and Loizou, 2008;Wang et al, 2008Wang et al, , 2009Cao et al, 2011;Sinex, 2013). This result should not be surprising, given the effectiveness of algorithm processing observed here and the fact that the algorithm aimed to estimate the IBM.…”
Section: Algorithm and Ibm Processingsupporting
confidence: 73%
See 3 more Smart Citations